2018
DOI: 10.1111/iwj.13018
|View full text |Cite
|
Sign up to set email alerts
|

Overview of psychosocial problems in individuals with stoma: A review of literature

Abstract: This literature review was conducted to summarise empirical evidence relating to psychosocial health following ostomy surgery during hospitalisation and after discharge. Both qualitative and quantitative studies were searched from 2000 to 2017 using PubMed, CINAHL, Ebrary, Elsevier, Science Direct, and Scopus. Twenty‐seven articles were included that examined the patient's psychosocial health following colostomy or ileostomy surgery. Among the 27 included studies, 11 adopted qualitative research methods and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
126
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(171 citation statements)
references
References 30 publications
(44 reference statements)
9
126
0
5
Order By: Relevance
“…Body image is often negatively influenced in patients with cancer by physical changes caused by the disease or treatment, such as after surgery for breast or colorectal cancer (eg, mastectomy, colostomy). 30,31 Specifically for patients with pancreatic and periampullary cancer, body image may be affected by the occurrence of cachexia. 32 The incidence of cachexia in patients with pancreatic cancer is high, cachexia-related complications occur often, and cachexia has been associated with reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…Body image is often negatively influenced in patients with cancer by physical changes caused by the disease or treatment, such as after surgery for breast or colorectal cancer (eg, mastectomy, colostomy). 30,31 Specifically for patients with pancreatic and periampullary cancer, body image may be affected by the occurrence of cachexia. 32 The incidence of cachexia in patients with pancreatic cancer is high, cachexia-related complications occur often, and cachexia has been associated with reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that an ostomy negatively influences a patient's quality of life and lifestyle (Näsvall et al., 2017; Vonk‐Klaassen, de Vocht, den Ouden, Eddes, & Schuurmans, 2016), including as a result of ostomy‐related problems, such as physical and sexual problems, depression, dissatisfaction with appearance and body image, changes in clothing, travel difficulties, and decreased work activities (Ayaz‐Alkaya, 2019; Vonk‐Klaassen et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This has a negative impact on their self-esteem and HRQoL [11]. Regardless of the time passed since the stoma formation, obstacles to QoL fall in one of the three categories: ostomy-related concerns and impact on life, limitations in physical and social activities, and negative impact on physical and mental health [12]. The time passed since the surgery also has a major impact on the QoL of persons with ostomy [13].…”
Section: Introductionmentioning
confidence: 99%